(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: Medical education is challenging which poses significant concern of mental health issues of medical students, especially first year medical students. Mental health assessment of first year MBBS students helps in management of mental health issues like stress, anxiety and depression. Material and methods: The Depression Anxiety Stress Scales (DASS-21) is a widely used scale for assessing psychological distress. This study examines changes in stress, anxiety, and depression scores among 1st year medical students of 2015 (n = 130) and 2025 (n = 218) batches using raw subscale totals from self-reported data. Result: Statistical analysis shows mean increases across all subscales: stress from 6.22 to 7.31, anxiety from 4.84 to 6.81, and depression from 4.36 to 5.58. Severity distributions shifted toward higher levels, particularly for anxiety (e.g., extremely severe from 6.2% to 28.4%). Independent samples t-tests confirmed statistically significant differences (p < 0.01 for all). Conclusion: These findings match with broader trends in mental health deterioration after COVID-19 pandemic, highlighting the need for ongoing monitoring and interventions. Possible stressor can also be changed medical education curriculum in form of CBME.